Corporate social responsibility disclosure before and during the Covid-19 pandemic - Cahyaningsih Cahyaningsih; Asty Septyaweni (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2022)
The COVID-19 pandemic has had a significant impact on the condition of the Indonesian economy, including the manufacturing industry. Therefore, it is necessary to test the effect of tax aggressiveness, environmental performance, and media exposure on corporate social responsibility disclosure. Corporate social responsibility disclosure is measured using the criteria set out in the 2017 Financial Services Authority (OJK) regulation. This study used 77 observational data from the 2017–2020 period in which the descriptive statistical analysis showed a decrease in tax aggressiveness, environmental performance, media exposure, and corporate social responsibility disclosure. The results showed significant differences in the manufacturing companies' corporate social responsibility disclosures before and during the COVID-19 pandemic. The findings revealed that tax aggressiveness and environmental performance positively affected corporate social responsibility disclosure. In contrast, media exposure did not affect corporate social responsibility disclosure. However, media exposure positively affected environmental aspects disclosure. These results indicated that manufacturing companies have social and environmental awareness.